Analisis dan Perancangan Sistem Informasi Akuntansi Pengelolaan Tabungan Siswa pada SD Ar-Raudah Bandarlampung - Damayanti, Damayanti; Sulistiani, H; Umpu, E F G S (Jurnal Teknologi dan Informasi (JATI), 2021)
Application of information technology in an organization is very important to facilitate and accelerate the management of activities that occur. This is the basis for the development of accounting information systems for managing student savings at SD Ar-Raudah Bandarlampung. Management of student savings is still done manually so that calculation errors often occur, filling in data when reporting savings and less responsive when searching for data. In addition, administrative staff also needs a long time to produce savings reports per student and overall savings report. The purpose of developing student savings information system is to facilitate administration staff in making reports and to minimize errors in recording student savings.